Study on external treatment of Traditional Chinese Medicine in the treatment of opioid-induced constipation (中医外治法在阿片类药物相关性便秘中的研究) - LI Guomin (李国敏); GONG Yang (龚杨); FU Yanli (付艳丽); ZHONG Yinqin (钟印芹); DENG Jinfeng (邓金凤); LIU Ying (刘莹); CHEN Jie (陈洁) (Association of Integrative Nursing, 2023)
Cancer patients frequently experience pain as a result of their cancer treatment. opioid-induced constipation (OIC) is a highly prevalent side effect in cancer pain sufferers that hurts their quality of life and enhances their risk of developing cardiovascular and cerebrovascular disorders. The effective prevention and treatment of OIC have vital clinical implications. This study summarized advances in the Traditional Chinese Medicine (TCM) etiology of cancer pain OIC and recent developments in external TCM treatment, and anticipations to assist as a reference for optimizing TCM interventions, as well as the cancerous pathogenesis provided by OIC, conduct a scientific investigation of pain. (阿片类药物是临床治疗癌性疼痛的常见药物, 阿片类药物相关性便秘(OIC)在癌痛患者中十分普遍, 严重影响患者的生存质量并有诱发心脑血管事件的风险, OIC的防治具有重要临床意义。本文归纳、总结了近年来癌痛OIC的中医病机认识及针刺、耳穴压贴、艾灸、穴位贴敷等中医外治法的相关进展, 旨在为癌痛OIC的中医药优化干预及科学研究提供参考。)